Boosting plant immunity with CRISPR/Cas. Issue 1 (December 2015) - Chaparro-Garcia, Angela; Kamoun, Sophien; Nekrasov, Vladimir
Abstract CRISPR/Cas has recently been transferred to plants to make them resistant to geminiviruses, a damaging family of DNA viruses. We discuss the potential and the limitations of this method. See related Research:http://www.genomebiology.com/2015/16/1/238